1987
DOI: 10.1029/ja092ia06p06045
|View full text |Cite
|
Sign up to set email alerts
|

Thermospheric dynamics during the March 22, 1979, magnetic storm: 1. Model simulations

Abstract: The physical processes involved in the transfer of energy from the solar wind to the magnetosphere and its release associated with substorms on March 22, 1979, have been studied in detail by the Coordinated Data Analaysis Workshop 6 (CDAW 6). The information derived from the CDAW 6 study, as well as other information obtained from magnetospheric modeling, is used to prescribe the time‐dependent variations of the parameterizations for the auroral and magnetospheric convection models that are incorporated within… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
31
0

Year Published

1989
1989
2005
2005

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(36 citation statements)
references
References 65 publications
5
31
0
Order By: Relevance
“…Buonsanto et al, 1989) and models (e.g. Roble et al, 1987;FullerRowell et al, 1996), and are consistent with the observed uplifting of the F-layer height at the mid-latitude radars, e.g. Irkutsk and Kharkov in Fig.…”
Section: Plasma Drifts and Their Effectssupporting
confidence: 71%
“…Buonsanto et al, 1989) and models (e.g. Roble et al, 1987;FullerRowell et al, 1996), and are consistent with the observed uplifting of the F-layer height at the mid-latitude radars, e.g. Irkutsk and Kharkov in Fig.…”
Section: Plasma Drifts and Their Effectssupporting
confidence: 71%
“…Roble et al [ 19781 reported observations of a day-time equatoward propagating disturbance of about three hours duration following a sudden storm commencement on Sept. 18,1974. A similar surge was found by Roble et al [1987a] in their simulations of the storm of March 2%…”
Section: Ion-neutral Diffuriorr Coemientsupporting
confidence: 54%
“…Roble et al [ 19781 reported observations of a day-time equatoward propagating disturbance of about three hours duration following a sudden storm commencement on Sept. 18,1974. A similar surge was found by Roble et al [1987a] in their simulations of the storm of March 2%1979. Thus it appears that the occurrence of day-time equatorward surges in the meridional neutral wind during storms may be a consistent feature of thermospheric dynamics.…”
supporting
confidence: 60%
See 1 more Smart Citation
“…These data have been analyzed by many authors, including Rees et al (1986) and Roble et al (1987Roble et al ( , 1988a using their thermospheric general circulation models. A good general agreement has been found between TGCMpredicted neutral winds and DE-2 observations showing the dominant in¯uence of magnetospheric convection on high-latitude circulation.…”
Section: Comparison With the Observationsmentioning
confidence: 99%